Changes in liver steatosis evaluated by transient elastography with the controlled attenuation parameter in HIV‐infected patients. Issue 10 (November 2016) - Macías, J; Real, LM; Rivero‐Juárez, A; Merchante, N; Camacho, A; Neukam, K; Rivero, A; Mancebo, M; Pineda, JA
Abstract : Objectives: There are scant data on the progression of hepatic steatosis (HS) in HIV infection. We therefore evaluated changes in HS over time in HIV‐infected patients using the controlled attenuation parameter (CAP). Methods: A prospective cohort of 326 HIV‐infected patients was included in this study. All patients underwent a CAP measurement. Changes in steatosis were evaluated by calculating the median (Q1–Q3) difference between baseline and 12‐month CAP values. Results: The median (Q1–Q3) CAP was 221 (196–252) dB/m at baseline and 224 (198–257) dB/m at the 12‐month visit ( P = 0.617). Significant steatosis, that is, CAP ≥ 238 dB/m, was observed in 76 individuals (37%) at baseline and in 80 (39%) at the 12‐month visit ( P = 0.683). The following variables were associated with ΔCAP: plasma HIV RNA [< 50 vs . ≥ 50 HIV‐1 RNA copies/mL: median (Q1–Q3) ΔCAP, 4 (−21, 27) vs . −21 (−49, 4) dB/m, respectively; P = 0.024]; body mass index (BMI) [no increase vs . increase: −13 (−40, 4) vs . 14 (−6, 32) dB/m, respectively; P < 0.001]; triglycerides [no increase vs . increase: −1 (−30, 22) vs . 15 (−3, 40) dB/m, respectively; P = 0.001]; fasting plasma glucose [not impaired vs . impaired: −4 (−31, 16) vs . 30 (15, 49) dB/m, respectively; P < 0.001]; and raltegravir [no vs . yes: 5 (−20, 29) vs . −11 (−37.5, 15) dB/m, respectively; P = 0.018]. The only factor independently associated with ΔCAP was BMI [B (standard error): 9.03 (1.9); P < 0.001]. Conclusions: Increases in CAP values over a period of 12 months in HIV‐infected patients were strongly associated with elevations in BMI. Other metabolic factors and antiretroviral drugs were not predictors of CAP changes independent of BMI.